Improving management of paracetamol overdose: a software solution. Issue 1 (12th December 2014) - Stewart, Michael; Robinson, Alison; Curran, Andy
Abstract : Objective: Paracetamol overdose is a common presentation to UK emergency departments, and national audits consistently identify shortfalls in the management of these patients. This study assesses the potential of a web-based computer application to improve the assessment and treatment of these patients. Methods: A retrospective cohort of patients was identified and their actual management and that advised by the software were assessed against current guidelines. Results: The application gave correct advice in all cases, significantly outperforming both actual treatment when the patients originally presented, and national performance based on previous College of Emergency Medicine audits. Conclusions: Advice from custom-written software outperforms actual treatment of patients presenting after paracetamol overdose.